The Perceptions and Concerns of Parents Who Have a Child With Developmental Coordination Disorder - Hitchcock, Brigid (Auckland University of Technology, 2020)
This qualitative descriptive study aimed to explore the perceptions and concerns of parents who have a child with Developmental Coordination Disorder (DCD). DCD is a neuro-developmental disorder in which a child’s motor skills are delayed. This can have an adverse impact on their activities of daily living, academic achievement and mental health. DCD impacts approximately 5-6% of children attending school and affects both the individual and their family. Although there are multiple studies on the disorder and its consequences for the individual, little is known about the perceptions of parents who have a child with DCD, particularly within a New Zealand context. The study investigated the question: “What are parents’ perceptions and concerns when raising a child with DCD?” and in doing so explored how parents came to know their child had coordination difficulties, the impact this disorder had on their child and family, as well as what strategies were implemented and actions taken to support their child. The child’s participation in occupations (home, school and extra-mural) and how these were influenced by DCD was central to this research. Interpretive description methodology was used and in keeping with this approach, participants were recruited through purposive sampling via the Dyspraxia Support Group of New Zealand. The nine participants, all women, selected to participate met the inclusion criteria of being a parent of a child, aged 5-12 years who had a formal diagnosis of DCD. Some of the children had additional diagnoses of ADHD and/or dyslexia, these are common comorbidities. Data were gathered using in-depth, semi-structured, telephonic interviews. The interviews were audio-taped and full text transcripts produced for analysis. In-depth reading of transcripts and coding of meaningful units were used to identify emergent themes. The findings of this study suggest that parents were aware from when their child was young, that they were different. These differences initially related to a delay in motor skills but later impacted significantly on the child’s academic achievement as well as their social and emotional wellbeing. Due to the perceived lack of knowledge of the disorder amongst professionals, participants reported that they worked hard to advocate for their child so that their needs could be understood and addressed. Parents faced challenges in both the health care and education sectors. The findings of the study were in keeping with those of international studies, which emphasise the struggle these children have with everyday self-care and academic tasks and the fact they participate less in physical and social activities than their typically developing peers. Secondary effects of DCD such as low self-esteem, anxiety and depression were also common amongst this group of children and this gives strength to the argument that children with DCD do require support. The implications of the study for parents are that their concerns are acknowledged and that the actions they took to support their children are shared by other mothers. For professionals dealing with these children, in healthcare and education, there is the need to be the aware that both parents and children are looking for understanding and support and thirdly, for researchers there is the call for further research into DCD, particularly looking at guidelines for identification and interventions which align with parents’ concerns. It is hoped that these findings can help expand the knowledge base regarding the impact of DCD and from there create a better understanding of the needs of these children to help mitigate harm, such as restricted participation in occupations, social isolation and depression, particularly within a New Zealand context.
Keywords: Developmental; Coordination; Children; Childhood Occupations